2018
DOI: 10.1039/c8ew00401c
|View full text |Cite|
|
Sign up to set email alerts
|

Non-target mass spectrometry analysis of NDMA precursors in advanced treatment for potable reuse

Abstract: Non-target high-resolution mass spectrometry was used to track the occurrence and removal of NDMA precursors during advanced treatment for reuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…NDMA is particularly challenging for facilities purifying municipal wastewater effluents for potable reuse. The full advanced treatment (FAT) train frequently employed at these facilities consists of microfiltration (MF) and reverse osmosis (RO) membranes as physical barriers to contaminants, followed by an UV-based advanced oxidation process (AOP) as a photochemical barrier. , NDMA concentrations in sewage or primary effluents can be ≥30 ng/L. , NDMA precursors are associated with wastewater effluents, and the chloramines applied to control biofouling on MF and RO membranes react with these precursors to form NDMA upstream of RO treatment. Because NDMA is only partially rejected by RO membranes, , the AOP employs up to 1000 mJ/cm 2 UV fluence to reduce the NDMA concentrations in RO permeates to <10 ng/L. ,, …”
Section: Introductionmentioning
confidence: 99%
“…NDMA is particularly challenging for facilities purifying municipal wastewater effluents for potable reuse. The full advanced treatment (FAT) train frequently employed at these facilities consists of microfiltration (MF) and reverse osmosis (RO) membranes as physical barriers to contaminants, followed by an UV-based advanced oxidation process (AOP) as a photochemical barrier. , NDMA concentrations in sewage or primary effluents can be ≥30 ng/L. , NDMA precursors are associated with wastewater effluents, and the chloramines applied to control biofouling on MF and RO membranes react with these precursors to form NDMA upstream of RO treatment. Because NDMA is only partially rejected by RO membranes, , the AOP employs up to 1000 mJ/cm 2 UV fluence to reduce the NDMA concentrations in RO permeates to <10 ng/L. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals have received global attention because of their persistence in aquatic environments and deleterious effects on aquatic life (Brausch & Rand, 2011; Gogoi et al, 2018; Yang et al, 2017). Pharmaceuticals are poorly removed by conventional wastewater treatment plants (Roback et al, 2018; Sharma et al, 2020; Zupanc et al, 2013) resulting in their occurrence in groundwater, lakes, foodstuff, and even in drinking water at concentrations from low ng/L to µg/L (Boyd et al, 2003; Ebele et al, 2017; Gogoi et al, 2018; Kolpin et al, 2002; McEachran et al, 2016; Poustie et al, 2020; Sharma et al, 2020; Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although RO is highly effective at removing organic compounds (e.g., 99% removal of total organic carbon), Roback et al showed that NDMA precursors are not fully removed by RO, where typical removal was ∼90%. 17,19 During subsequent UV-AOP, if the remaining precursors are not sufficiently removed or if new precursors are formed, the NDMA concentration has the potential to rebound after UV-AOP in the finished water despite NDMA being reduced to nondetectable levels by the UV-AOP. 19,20 NDMA rebound can occur as a result of the post-treatment stabilization process because NDMA formation is favored at higher pH.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that wastewater is enriched with secondary and tertiary amines and that effluent organic matter (EfOM) from wastewater contains NDMA precursors. However, the specific precursors responsible for the majority of NDMA formed in treated wastewaters are unknown. Several studies have isolated and identified specific precursors in wastewater, but on the basis of their low occurrence and typically low yields, ,,, the authors hypothesize that the precursors identified to date do not explain the levels of NDMA that form in treated wastewater. Hence, it is possible that a wide range of precursors, each occurring at low concentrations, are together responsible for the measured NDMA that forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation